A computational algorithm for the loss probability in the M/G/1+PH queue. Issue 1 (2nd January 2017) - Inoue, Yoshiaki; Takine, Tetsuya
ABSTRACT: This article develops a computational algorithm for the loss probability in the stationary M/G/1 queue with impatient customers whose impatience times follow a phase-type distribution (M/G/1+PH). The algorithm outputs the loss probability, along with an upper-bound of its numerical error due to truncation, and it is readily applicable to the M/D/1+PH, M/PH/1+PH, and M/Pareto/1+PH queues.